EFEKTIVITAS METODE PRAKTIKUM PENGUKURAN TERHADAP HASIL BELAJAR PSIKOMOTORIK SISWA MTs BAHRUL ULUM ROKAN HULU RIAUâ - Novianti, Ade Irma (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2016)
This research aims to determine the psychomotor abilities of students in learning physics by doing lab-based performance assessment. This type of research is descriptive quantitative research design One-Shot Case Study. The sampling technique that is done is saturated sampling technique. The research was conducted in Bahrul Ulum MTs Rambah Downstream class VII. The first and second meetings conducted by sheet guiding practicum (LPP) assessment and observation sheet. The third meeting of assessment using performance assessment. At the first meeting of LPP lowest value for the class VII is 70 namely the LPP 5. The highest value for the class VII is 85, namely group 3. Observations on the second meeting for the seventh grade have an average activity of excellent quality. At the third meeting of psychomotor ability of students to use student performance assessment for the whole class VII effectively. So it can be concluded that the method of measurement practicum effectively used in learning.Â